METODE PENANAMAN NILAI-NILAI KARAKTER RELIGIUS SANTRI DI MA’HAD TAHFIZUL QUR’AN AL-FIRQAH AN-NAJIYAH KARANGPLOSO MALANG - Yudi Hardiyani (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The cultivation of the religious character of values is something that is relatively long in the world of Islamic education. This was seen to need to be realized, especially the values that direct contact with the formation of a moral nation.This study aims to reveal character values ilai Planting religious students who instilled in Ma'had Tahfizul Quran Al-Firqah An-Najiyah Karangploso Malang and methods used in instilling the values of the religious character of the students in Ma'had Tahfizul Quran Al-Firqah An-Najiyah Karangploso Malang. This study used a qualitative approach. Data collection is done with the interview techniques, observation and documentation. Data analysis techniques include the collection of data, data education, data presentation, and withdrawal of the conclusion, validity checking of the data is done by way of an extension of the participation of researchers: triangulation techniques using a variety of sources, theory and methods, and persistence of observation research information i.e. whole ustadz as well as students.The results showed that: (1) the cultivation of the values of the religious character of the students at Ma'had Al-Firqah Tahfizul Quran An-Najiyah karangploso Malang, include some value is: (a) religious, (b) honest, (c) tolerance, (d) discipline, (e) of hard work, (f) independent, (g), peace-loving, (h) caring environment, (i) the value of the religious character of responsibility, (j) nasinalisme/spirit of nationality, (k) love the motherland, j) communicative, friendly, happy (l) appreciate your achievements, (m) social care , (n) tough, (o) manners,(p) clean, (q) frugal ,(r) efficient patient. (2) the method of cultivation of the values of the religious character of the students at Ma'had Al-Firqah Tahfizul Quran An-Najiyah karangploso Malang, includes several methods, are: (a) example, (b) habituation, (c) conditioning advice, (d) prohibitions and orders, (e) story-telling, (f) memorizing.